Java web services up and running - Kalin, Martin (O'Reilly, 2009)
Introduction to Java's APIs for both XML Web Services (JAX-WS and RESTful Web Services (JAX-RS) provides a pragmatic approach, architectural overview, working code examples, and instructions for compiling, deploying, and executing an application. -- from cover, p.4.